Efektivitas Model Pembelajaran Tutor Sebaya Berbantuan CD Interaktif Terhadap Hasil Belajar Instalasi Sistem Operasi - Suci Lestary; Kholida Ismatullah; Rasyid Hardi Wirasasmita (Universitas Hamzanwadi, 2019)
This study aims to determine the effectiveness of peer tutoring learning models assisted by interactive CD on the learning outcomes of students of SMKN 3 Selong. The population in this study were all students of class X TKJ SMKN 3 Selong 2018/2019 academic year. The sample collecting technique in this study used saturated samples, where the samples in this study is the class X TKJ-1 as the experimental class with the number of students 30 and class X TKJ-2 as the control class with a total of 31 students, the two classes treated different,the experimental class uses peer tutoring learning models and the control class uses conventional learning models (lectures). The technique used to collect data is a tests that server to measure student learning outcomes. The data analysis technique used is the independent sample test t-tes with the help of SPSS. The results of this study indicate that the peer tutoring learning model is effective against the learning outcomes of open source operating system instalations in Selong 3 vocational school (significant with Ï value 0,05), from the results of this hypothesis calculation sig Ï 0,05, which is 0,000 0,05.